Investigating the Differences of Small Enterprise supply chain managements toward Financial Performance: The Influence of an Enterprise Supply Chain Management Strategy - Husnah Husnah; Sari Wahyuni (International Journal of Supply Chain Management, 2020)
The purpose of this study is to critically analyse the impact of demographic characteristics and the way investors choose risk (tolerance) toward financial performance as exemplary for the integrity of enterprise supply chain management upgrading strategies. The demographic characteristics of Micro Small Medium Enterprise supply chain managements (MSME) are assessed, which consist of the type of business, gender, age of owner, age of business, education, and experience. Risk tolerance is measured by assessing the choices of risk averters, risk neutrals, and risk seekers. This study is based on 579 questionnaires filled in by the owners or managers of MSMEs that obtain credit financing from banks in Central Sulawesi, Indonesia (Kota Palu, Sigi, Banggai, Donggala, Morowali, Parigi Moutong, and Poso). The results of this study show the demographic characteristics of the types of trading businesses that are risk seekers, which proved to be the highest type of business that can maximize their financial performance. Notably, males were shown to prefer being risk averse, compared to the majority of female respondents who were mostly risk seekers. Resultingly, many women have high financial performance due to being risk seekers compared to men. Both young and elderly entrepreneurs are more risk averse. The age of the business is still categorised at the stage of business development, it has not been proven to have a significant relationship to risk tolerance and financial performance. Moreover, this study reveals that education apparently has no significant relationship in choosing risk. Education also has no significant relationship to the achievement of financial performance. Experience is suggested to be the key that determines risk tolerance choices and the main determinants of achieving optimal financial performance. This study proves the behavior of MSME investors in choosing risk (risk tolerance) makes a difference in achieving MSME financial performance. Contrastingly exemplified by the higher the risk chosen, the higher the financial performance is received by MSMEs. The integrity of demographic characteristics, risk tolerance and financial performance is a breakthrough for MSMEs to nurture upgrades as an enterprise supply chain management upgrading strategy.